(3GdJgPjH deSGFd GdeOhfIs - (3Nda Hf CHj GdbGSe eMeO, GdCROj, CHh SYjO GHf GdHQGPYj, J (B- 372 (3g` s; (3YHO GdQMef Hf GdbGSe Hf NGdO Hf LfGOI GdYJbqj GdeGdcj GdeUQj, CHh YHO Gddg, hjYQa HGHf GdbGSe,J (B191 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdChd GdHGbi HZjQ ZGjg s
(3BNQgG (B:s
(3BNQ GdehLhO efg (B: (3hdh cGf TQGDg fbOkG Ch Edi CeO bQjH aUH LGR s
(3GdfSNI HgG MhGTs
(3cJHJ Ydi Qb ZRGd aQZ ef fSN GdLRA GdQGHY efgG SfI (B535s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B283 ; (3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B283 ; (3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B681s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3Gdabg GdeGdcjs